The starfish and the spider : the unstoppable power of leaderless organizations. - Brafman, Ori, ....-; Beckstrom, Rod A., ....- (New York : Penguin, 2007)
If you cut off a spiders head, it dies; if you cut off a starfishs leg it grows a new one, and that leg can grow into an entirely new starfish. Traditional top-down organizations are like spiders, but now starfish organizations are changing the face of business and the world. Whats the hidden power behind the success of Wikipedia, craigslist, and Skype? What do eBay and General Electric have in common with the abolitionist and womens rights movements? What fundamental choice put General Motors and Toyota on vastly different paths? Ori Brafman and Rod Beckstrom have discovered some unexpected answers, gripping stories, and a tapestry of unlikely connections. "The Starfish and the Spider" explores what happens when starfish take on spiders and reveals how established companies and institutions, from IBM to Intuit to the U.S. government, are also learning how to incorporate starfish principles to achieve success.
Keywords: Leiderschap